2016
DOI: 10.3892/etm.2016.3475
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of etomidate and propofol anesthesia in elderly patients undergoing gastroscopy: A double-blind randomized clinical study

Abstract: Abstract. The aim of the present study is to compare the safety, efficacy and cost effectiveness of anesthetic regimens by compound, using etomidate and propofol in elderly patients undergoing gastroscopy. A total of 200 volunteers (65-79 years of age) scheduled for gastroscopy under anesthesia were randomly divided into the following groups: P, propofol (1.5-2.0 mg/kg); E, etomidate (0.15-0.2 mg/kg); P+E, propofol (0.75-1 mg/kg) followed by etomidate (0.075-0.1 mg/kg); and E+P, etomidate (0.075-0.01 mg/kg) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 25 publications
2
27
1
Order By: Relevance
“…[ 35 ] In addition, another study showed that a combination of etomidate and propofol improved hemodynamic stability and minimal respiratory depression during gastroscopy in the elderly. [ 36 ] However, there is no study on etomidate for colonoscopy in the elderly. For these reasons, we designed a comparison study in which etomidate can be used alternatively even in elderly patients during screening colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 35 ] In addition, another study showed that a combination of etomidate and propofol improved hemodynamic stability and minimal respiratory depression during gastroscopy in the elderly. [ 36 ] However, there is no study on etomidate for colonoscopy in the elderly. For these reasons, we designed a comparison study in which etomidate can be used alternatively even in elderly patients during screening colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of MAP was better with sevoflurane compared with propofol. Although the difference may be of limited significance for healthy patients, the relative hypotension associated with propofol may be detrimental in elderly patients and patients with coronary artery disease (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…With the aging of the general population, the frequency of this procedure in the elderly is increasing rapidly [2,3]. Although it is a non-traumatic invasive procedure, it often results in significant discomfort in the majority of patients, requiring sedation during the thorough examination [4]. Currently, sedation during upper gastrointestinal endoscopy is mainly obtained by using either propofol or a benzodiazepine, sometimes in combination with an analgesic [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Remimazolam tosilate in patients undergoing upper gastrointestinal endoscopy: a multicenter, randomized, dose-exploration, positive-controlled, parallel-group, phase II trial Shao-Hui Chen 1 , Tang-Mi Yuan 1 , Jiao Zhang 1 , Hua Bai 2 , Ming Tian 3 , Chu-Xiong Pan 4 , Hong-Guang Bao 5 , Su Min 6 , Xiao-Ju Jin 7 , Guo-Zhong Chen 8 , Tai-Di Zhong 9 , Yu-Guang Huang 1…”
mentioning
confidence: 99%